The rice E3 ubiquitin ligase-transcription factor module targets two trypsin inhibitors to enhance broad-spectrum disease resistance - Zhang, Chongyang; Fang, Hong; Wang, Jisong; Tao, Hui; Wang, Debao; Qin, Mengchao; He, Feng; Wang, Ruyi; Wang, Guo-Liang; Ning, Yuese (Developmental cell, 2024)
Broad-spectrum disease resistance (BSR) is crucial for controlling plant diseases and relies on immune signals that are subject to transcriptional and post-translational regulation. How plants integrate and coordinate these signals remains unclear. We show here that the rice really interesting new gene (RING)-type E3 ubiquitin ligase OsRING113 targets APIP5, a negative regulator of plant immunity and programmed cell death (PCD), for 26S proteasomal degradation. The osring113 mutants in Nipponbare exhibited decreased BSR, while the overexpressing OsRING113 plants showed enhanced BSR against Magnaporthe oryzae (M. oryzae) and Xanthomonas oryzae pv. oryzae (Xoo). Furthermore, APIP5 directly suppressed the transcription of the Bowman-Birk trypsin inhibitor genes OsBBTI5 and AvrPiz-t-interacting protein 4 (APIP4). Overexpression of these two genes, which are partially required for APIP5-mediated PCD and disease resistance, conferred BSR. OsBBTI5 and APIP4 associated with and stabilized the pathogenesis-related protein OsPR1aL, which promotes M. oryzae resistance. Our results identify an immune module with integrated and coordinated hierarchical regulations that confer BSR in plants. [Display omitted] •OsRING113 ubiquitinates APIP5 to enhance broad-spectrum disease resistance•OsBBTI5 and APIP4 repressed by APIP5 are required for APIP5-mediated regulation•OsRING113 attenuates APIP5-mediated OsBBTI5 and APIP4 repression•OsBBTI5 and APIP4 stabilize OsPR1aL to enhance rice immunity Zhang et al. demonstrate that the E3 ubiquitin ligase OsRING113, a positive regulator of broad-spectrum disease resistance, ubiquitinates and targets the negative regulator of programmed cell death APIP5 for degradation. The transcription factor APIP5 normally represses the expression of OsBBTI5 and APIP4, which results in stabilizing the defense-related protein OsPR1aL and enhancing immunity.